THE IMPLEMENTATION OF SAS (SINTETIC ANALITYC STRUCTURAL) METHOD TO INCREASE THE BEGINNER READING ABILITY AT THE THIRD GRADE STUDENTS’ OF SDN 28 MATARAM - Muhammad Asrul Hasby (Sinar Lima, 2024)
This research is motivated by the low reading ability of students in class 3B Elementary School Negeri of 28 Mataram,West Nusa Tenggara. One solution to solve this problem is to use the synthetic structural analysis (SAS) method. The purpose of this study was to describe the improvement of students' initial reading skills using the synthetic structural analytical method (SAS) in third grade students of SDN 28 Mataram. This research method is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, reflection. The subjects of this study were 3B students of SDN 28 Mataram, totaling 20 students. The collection technique is in the form of observation, test, and documentation. The results of this study can be concluded that the ability to read at the beginning of class 3B SDN 28 Mataram in the first cycle of students who completed 14 students or 70%, and in the second cycle students who completed the whole were 17 students or 85%. Thus, it can be concluded that using the synthetic structural analytical method (SAS) can improve reading ability at the beginning of class 3B at SDN 28 Mataram.